Dual functions of ILs in the core-shell particle reinforced epoxy networks: Curing agent vs dispersion aids. (1st March 2017) - Nguyen, Thi Khanh Ly; Soares, Bluma G.; Duchet-Rumeau, Jannick; Livi, Sébastien
Abstract: We present herein a comparative study on the dispersion of a commercial core-shell rubber particles denoted Genioperl P52 (CSR) in the epoxy networks cured with conventional amine 4, 4'-methylene bis(3-chloro-2, 6-diethylaniline) (MCDEA) and with two phosphonium ionic liquids (ILs) denoted: trihexyl (tetradecyl) phosphonium bis-2, 4, 4-(trimethyl pentyl) phosphinate (IL-TMP) and tributyl (ethyl) phosphonium (diethyl) phosphate (IL-DEP). Epoxy networks containing 10 and 20 phr of CSR were prepared and the effect of CSR on the final properties of epoxy networks was evaluated. We have demonstrated that the chemical nature of ILs play a key role on the morphology of modified epoxy networks resulting in a better dispersion of CSR compared to epoxy/amine networks. In addition, a correlation between morphology and properties of epoxy networks was also revealed in terms of thermal, mechanical properties as well as the hydrophobic behavior. In fact, a better distribution of CSR particles into epoxy/ILs networks led to an increase in fracture toughness compared to modified epoxy/amine networks i.e . 27% and 54% higher of KIc for DGEBA/MCDEA and DGEBA/IL-DEP system modified by 20 phr of CSR particles, respectively. Nevertheless, the toughening mechanism can also be influenced by the interaction between cured epoxy matrix and CSR particles.